Optimum Taxation and the Allocation of Time. - Henrik Jacobsen Kleven (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
This paper deals with optimum commodity taxation in Becker's (1965) model of the allocation of time. While the existing public finance literature emphasizes the role of cross elasticities with leisure, I find that the optimal tax system crucially depends on factor shares and elasticities of substitution in household production. In the special case of Leontieff technology, the optimum tax rule depends solely on factor shares and, furthermore, this simple rule maintains the first best allocation. The Becker approach implies, for example, that the social optimum involves a preferential tax treatment of consumer services and possibly even exclusion from the tax base.
Keywords: 330